USE INFORMATION TECHNOLOGY IN THE PROCESS OF PERFORMING PHYSICAL ACTIVITY IN PRESCHOOLERS - Gulbahor Yuldasheva; Muhammedova Mohidilxon (American Journals Publishing, 2024)
This article will consider examples of the use of information and communication technologies in the field of physical development in a preschool organization.
Keywords: Preschool education, information communication tools, physical development.